Aquinói Szent Tamás az igazságos háborúról, a fegyveres önvédelemről, a zsarnokölésről és a halálbüntetésről – a szeretet, a béke és az emberi élet legfőbb értékeinek perspektívájából - Frivaldszky, János (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The doctrine of just war, despite centuries of popular belief, does not play a dominant role in the Angelic Doctor’s moral theology, and instead we must reassess the centrality of peace. He certainly did not exalt just war, and especially not punitive war. We must take seriously the concept of ʻtwo effectsʼ in interpreting legitimate self-defence, even if it raises theoretical and practical problems. Otherwise it will not be clear that the aim is to protect life and not to kill the aggressor. The defence of human life is not only against the tyrant’s arbitrary power, but St Thomas gives arguments why the tyrant should not be killed either, and how it is worth preventing him from attacking the lives of his subjects. In the case of the tyrant, the argument is not to protect his life, but nevertheless nothing really good comes from killing the despot. St Thomas Aquinas does not believe in the good that comes from killing people. Therefore, in the most exceptional cases, he is only willing to consider its necessity or justification. As to the death penalty, we already know that man cannot lose his dignity, since his spiritual soul remains incorruptible whatever sins he may commit, and therefore the punishment to be inflicted cannot be capital punishment. Community self-defence against him can no longer be a consideration, since the system of secure punishment precludes it.